2002
DOI: 10.1038/sj.onc.1205169
|View full text |Cite
|
Sign up to set email alerts
|

PARP-1 modifies the effectiveness of p53-mediated DNA damage response

Abstract: The tumour supressor protein p53 plays a key role in the cell's decision to arrest the cell cycle or undergo apoptosis following a genotoxic insult. p53 is stabilized and activated after DNA damage, however the cascade of events signalling from DNA lesions to p53 stabilization and activation is still controversial. Poly (ADPribosylation) of dierent nuclear acceptors by PARP-1 is an early event when a single strand DNA lesion is produced. We present here evidences that interplay between PARP-1 and p53 is depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
70
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(76 citation statements)
references
References 35 publications
(30 reference statements)
4
70
0
Order By: Relevance
“…The remaining chromatin-associated interactions identified by in-solution digestion will be described in a separate publication. This link is notable in light of previous findings that FKBP25 regulates p53 levels via MDM2 (Ochocka et al 2009), and KAP1, PARP1, and RPA1 all have links to the regulation of p53 in DNA damage (Valenzuela et al 2002;Bochkareva et al 2005;Wang et al 2005). In support of a potential role for FKBP25 in chromatin biology, histone deacetylaces (HDAC) 1 and 2 have been identified as FKBP25-associated proteins (Yang et al 2001), and Mybbp1a and KAP1 are found in complexes containing HDAC1 and 2 (Schultz et al 2001;Tan et al 2012).…”
Section: Fkbp25 Localizes To the Nucleus And Nucleolus And Associatesmentioning
confidence: 90%
“…The remaining chromatin-associated interactions identified by in-solution digestion will be described in a separate publication. This link is notable in light of previous findings that FKBP25 regulates p53 levels via MDM2 (Ochocka et al 2009), and KAP1, PARP1, and RPA1 all have links to the regulation of p53 in DNA damage (Valenzuela et al 2002;Bochkareva et al 2005;Wang et al 2005). In support of a potential role for FKBP25 in chromatin biology, histone deacetylaces (HDAC) 1 and 2 have been identified as FKBP25-associated proteins (Yang et al 2001), and Mybbp1a and KAP1 are found in complexes containing HDAC1 and 2 (Schultz et al 2001;Tan et al 2012).…”
Section: Fkbp25 Localizes To the Nucleus And Nucleolus And Associatesmentioning
confidence: 90%
“…For instance, several studies using either PARP inhibitors or PARP knockout (KO) mice demonstrate the important role of this protein in maintaining DNA integrity, 12 and several benzamide-derived PARP inhibitors are being tested to treat cancer patients. 13,14 One of the targets of PARP-1 is p53, [15][16][17][18] promoting its poly(ADPribosyl)ation and accumulation in the nucleus, to control its transcriptional activity. However, hyperactivation of PARP-1 after severe DNA damage can cause NAD and ATP depletion leading to a unique form of necrotic cell death named parthanatos.…”
mentioning
confidence: 99%
“…13,14 One of the targets of PARP-1 is p53, [15][16][17][18] promoting its poly(ADPribosyl)ation and accumulation in the nucleus, to control its transcriptional activity. However, hyperactivation of PARP-1 after severe DNA damage can cause NAD and ATP depletion leading to a unique form of necrotic cell death named parthanatos.…”
mentioning
confidence: 99%
“…PARP-1 is an abundant nuclear enzyme that binds to DNA single-strand breaks. This binding triggers its catalytic activity, the synthesis of ADP-ribose polymers, and their attachment to acceptor proteins including itself (7,8,(22)(23)(24)(25), thereby initiating such events as recruitment of DNA repair proteins (7,8,(26)(27)(28) and modulation of p53-and NF-B-dependent signaling pathways (29)(30)(31)(32)(33) or chromatin structure (34).…”
mentioning
confidence: 99%